2018
DOI: 10.1089/hum.2018.091
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of an HLA-DRB1*04-Restricted HPV16-E7 T Cell Receptor for Cancer Immunotherapy

Abstract: High-risk human papillomavirus (HPV) infection is a causal factor in oropharyngeal and gynecological malignancies, and development of HPV-targeted immunotherapy could be used to treat patients with these cancers. T cell-mediated adoptive immunotherapy targeting E6 and E7, two HPV16 proteins consistently expressed in tumor cells, appears to be both attractive and safe. However, isolation of HPV-specific T cells is difficult owing to the low frequency of these cell precursors in the peripheral blood. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Another study reported the isolation of an HLA-DRB1*04 restricted TCR reactive to the HPV16 E7 70-89 epitope. TCRtransduced cells were shown to specifically produce IFNg when stimulated with HPV16 E6 and E7 containing tumor lysate (160). The isolation of TCR responsive to HPV epitopes restricted by a series of HLA class I and II molecules will lead to a warehouse of HPV-specific TCR required for personalized treatment of patients with recurrent or metastatic HPV-induced OPSCC.…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
“…Another study reported the isolation of an HLA-DRB1*04 restricted TCR reactive to the HPV16 E7 70-89 epitope. TCRtransduced cells were shown to specifically produce IFNg when stimulated with HPV16 E6 and E7 containing tumor lysate (160). The isolation of TCR responsive to HPV epitopes restricted by a series of HLA class I and II molecules will lead to a warehouse of HPV-specific TCR required for personalized treatment of patients with recurrent or metastatic HPV-induced OPSCC.…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
“…Figure 1 is an example in which stimulation of PBMC with moDC-mock-HeLa led to non-zero, CD137-expressing CD4 and CD8 T cells, consistent with our previous publication ( 18 ). HPV-specific T cells are rare: in vitro elicitation of HPV E6 or E7-reactive T cells from PBMC uses repetitive cycles of re-stimulation with high concentrations of peptides ( 109 ), and in vivo vaccinations use many cycles of peptide-loaded DC ( 110 ). It would be possible to query our HSV-reactive T cell lines with HPV expression constructs ( 111 ) to detect HPV-specific reactivity in our system.…”
Section: Discussionmentioning
confidence: 99%
“…( 52 54 ). More recently, some groups combined VDJ sequencing and reference sequences from the ImMunoGeneTics database to identify functional TCRs ( 55 , 56 ). The development of single-cell RNA sequencing (scRNA-seq) focused on TCR sequences (scTCR-seq) has also facilitated the identification of TCRs from primed T cells.…”
Section: Tcr Identification and Optimizationmentioning
confidence: 99%